log(8)+log(x+9)=log(128)

Simple and best practice solution for log(8)+log(x+9)=log(128) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for log(8)+log(x+9)=log(128) equation:


Simplifying
log(8) + log(x + 9) = log(128)

Reorder the terms for easier multiplication:
8glo + log(x + 9) = log(128)

Reorder the terms:
8glo + glo(9 + x) = log(128)
8glo + (9 * glo + x * glo) = log(128)
8glo + (9glo + glox) = log(128)

Combine like terms: 8glo + 9glo = 17glo
17glo + glox = log(128)

Reorder the terms for easier multiplication:
17glo + glox = 128glo

Solving
17glo + glox = 128glo

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-128glo' to each side of the equation.
17glo + -128glo + glox = 128glo + -128glo

Combine like terms: 17glo + -128glo = -111glo
-111glo + glox = 128glo + -128glo

Combine like terms: 128glo + -128glo = 0
-111glo + glox = 0

Factor out the Greatest Common Factor (GCF), 'glo'.
glo(-111 + x) = 0

Subproblem 1

Set the factor 'glo' equal to zero and attempt to solve: Simplifying glo = 0 Solving glo = 0 Move all terms containing g to the left, all other terms to the right. Simplifying glo = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-111 + x)' equal to zero and attempt to solve: Simplifying -111 + x = 0 Solving -111 + x = 0 Move all terms containing g to the left, all other terms to the right. Add '111' to each side of the equation. -111 + 111 + x = 0 + 111 Combine like terms: -111 + 111 = 0 0 + x = 0 + 111 x = 0 + 111 Combine like terms: 0 + 111 = 111 x = 111 Add '-1x' to each side of the equation. x + -1x = 111 + -1x Combine like terms: x + -1x = 0 0 = 111 + -1x Simplifying 0 = 111 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 3(x+3)-5=5x-2(-4+x) | | 9x^2-3x+9=0 | | y=3+3sin(3x-7) | | 3m^2-3m-5=0 | | 20=-2/3x | | 0.12(y-5)+0.18y=0.20y-0.03(30) | | 9y=1/5 | | 2a+5a+18=0 | | 0.08(y-8)+0.06y=0.12y-0.01(50) | | 0.14(y-2)+0.16y=0.02y-0.01(70) | | x-11/2=19/6 | | 0.12(y-7)+0.14y=0y-0.01(20) | | k^2+10k-25=0 | | 7x+29=12x-3 | | x-13/2=17/10 | | -2(4t-4)+6t=5t-5 | | (X-3)(x-4)=12 | | x-20/3=8/15 | | 1/4(x-8)1/15(4x-1) | | x^2-x-55=0 | | -2(3x-3)+2=-6x+8 | | 3(6x+9)=18x+27 | | -5(3y-6)-y=-2(y-5) | | x/3.2=8 | | 5x+12y=0 | | x/3-5=20 | | -9+3=m-3 | | 2/8x-1/3=-1 | | (5x+6)2=49 | | 3k^2+7k-66=0 | | 20c^2-17c-63= | | x/6=5/13 |

Equations solver categories